Recurrent Aphthous Stomatitis: Current Concepts in Diagnosis and Management - V Vivek; Bindu J Nair (Journal of Indian Academy of Oral Medicine and Radiology, 2011)
Recurrent aphthous stomatitis (RAS) is one of the most common oral mucosal condition, but little is known of its etiology or pathogenesis. Several factors have been postulated to be the cause of this condition. Currently, the most widely accepted etiology is that RAS is a localized immunological disorder. The treatment modalities for RAS, till recently, were aimed at providing symptomatic relief. In spite of the fact that the condition is recurrent and common, till date there are no effective and definitive preventive treatment strategies. This article aims to summarize the current concepts of diagnosis and management of RAS.